Squirrel cage induction generator to 140 bus weak distribution power grid connection using i-UPQC for voltage fluctuations. (October 2019) - Reddy, K.V. Ramana; Ravi, K.; Shilaja, C.
Abstract: This paper develops an optimal power transmit strategy for 140 bus weak distribution power grid connecting squirrel cage induction generator (SCIG) and integrated unified power quality conditioner (i-UPQC). To meet technical standards and earn operational profits in electricity market can consequently increases the operational cost. As to decrease the operational cost basis, the optimal location of i-UPQC on 140 bus power system for voltage control can be determined. The integrated-proposed controller can modulate the predictions of weak power grid, maintenance cost, wind power and voltage fluctuations. The proposed model is validated using SCIG data for weak distribution power grid and i-UPQC capacity. Results address the effectiveness of the method and help to weak power grid to ensure optimal location and energy schedule. The results motivate weak power grid operators to adjust i-UPQC real and reactive output powers to overcome the power quality problem called weak power grid.